Digital multisided platforms and women's health: an empirical analysis of peer-to-peer lending and abortion rates - Ozer, Gorkem Turgut (2023)
Digital multisided platforms and peer-to-peer marketplaces are increasingly attracting attention from scholars, with a significant amount of work examining their societal implications. Despite such focus, limited work has investigated the social implications of the democratization of capital by peer-to-peer (P2P) lending platforms, particularly within the healthcare sector, where financial constraints can be daunting. In this study, we investigate the effects of P2P lending platforms on local abortion rates, a medical procedure characterized by significant financial barriers and social stigma. Leveraging the entry of the P2P platformLendingClub into different states at different times, and a differences-in-differences approach, we find that the entry of LendingClub is associated with an increase in the rate at which women choose not to carry to term. Further, results indicate the effects vary based on the characteristics of the local area, with stronger effects manifesting in more religious areas and areas with lower levels of education, suggesting that social frictions in the form of stigma and knowledge asymmetries can influence financial need. Theoretical and practical implications are discussedwithin.